Bruton’s Tyrosine Kinase (BTK) Inhibitor RN486 Overcomes ABCB1-Mediated Multidrug Resistance in Cancer Cells - Dong, Xing-Duo; Zhang, Meng; Ma, Xiubin; Wang, Jing-Quan; Lei, Zi-Ning; Teng, Qiu-Xu; Li, Yi-Dong; Lin, Lusheng; Feng, Weiguo; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2020)
Overexpression of ATP-binding cassette subfamily B member 1 (ABCB1) remains one of the most vital factors leading to multidrug resistance (MDR). It is important to enhance the effect and bioavailability of chemotherapeutic drugs that are substrates of ABCB1 transporter in ABCB1-overexpression cancer cells and reverse ABCB1-mediated MDR. Previous, we uncovered that the Bruton's tyrosine kinase (BTK) inhibitor ibrutinib is a potent reversal agent to overcomes paclitaxel resistance in ABCB1-overexpressing cells and tumors. In this study, we explored whether RN486, another BTK inhibitor, was competent to surmount ABCB1-mediated MDR and promote relevant cancer chemotherapy. We found that RN486 significantly increased the efficacy of paclitaxel and doxorubicin in both drug-selected carcinoma cells and transfected cells overexpressing ABCB1. Mechanistic studies indicated that RN486 dramatically attenuated the drug efflux activity of ABCB1 transporter without altering its expression level or subcellular localization. The ATPase activity of ABCB1 transporter was not affected by low concentrations but stimulated by high concentrations of RN486. Moreover, an interaction between RN486 with ABCB1 substrate-binding and inhibitor binding sites was verified by in silico docking simulation. The results from our study suggest that RN486 could be a reversal agent and could be used in the novel combination therapy with other antineoplastic drugs to conquer MDR-mediated by ABCB1 transporter in clinics.